Analytical study of a solution-processed diode based on ZnO nanoparticles using multi-walled carbon nanotubes as Schottky contact - Bertoldo, Luis H. T. [UNESP]; Nogueira, Gabriel L. [UNESP]; Vieira, Douglas H. [UNESP]; Klem, Maykel S. [UNESP]; Ozório, Maíza S. [UNESP]; Alves, Neri [UNESP] (My University, 2022)
The search for good electrodes processed by solution has interested several niches to produce printed solar cells, lighting emitting diodes, transistors, and photodetectors. In this context, carbon nanotube (CNT) has been reported as a promising electrode material, being suitable for several printing techniques such as inkjet, screen-printing, and spray-coating. Here, we present a successfully manufactured spray-deposited diode based on the Schottky junction between multi-walled carbon nanotubes (MWCNTs) and zinc oxide nanoparticles (ZnO-NPs), both deposited by spray. Using analytical methods, we estimated the diode series resistance as 6.2 kΩ and the ideality factor as 2.2. The good morphological characteristics of the ZnO-NP and MWCNT films resulted in a good interface, allowing the junction to achieve a high effective Schottky barrier height of 0.82 eV, high rectification ratio of 1 × 104, and low turn-on voltage of 0.55 V.